Enlightenment and revolution : the making of modern Greece - Kitromilides, Paschalis (Harvard University Press, 2013)
To comprehend how Greece precipitated such an outsized economic crisis in Europe, we must understand how it developed into a nation in the first place. Enlightenment and Revolution traces the ideologies that shaped a Greek-speaking religious community into a modern nation-state- one in which antiliberal forces have exacted a high price.